STEROIDS FROM THE SUPER RED DRAGON FRUIT (Hylocereus costaricensis) - H. Supriadi; S. Salam; F. F. Abdullah; A. Subarnas; R. Sidik; U. Supratman; Y. Shiono (Jurnal Kimia (Journal of Chemistry), 2019)
Two steroids compounds, 7?-Hydoxy ?-sitosterol (1) and ?-sitosterol (2), have been isolated from ethyl acetate extract of the fresh Super Red Dragon Fruit (Hylocereus costaricensis).The chemical structure of compounds 1 and 2 were identified by spectroscopic data including UV, IR, NMR-1D, NMR-2D and mass as well as by comparing with previously reported spectral data. Compounds 1 and 2 were reported for the first time from dragon fruit (Hylocereus costaricensis). Keywords: 7?-Hydoxy ?-sitosterol, ?-sitosterol, Hylocereus costaricensis, steroids.